The Effect Of Training And Competency On Work Performance With Job Promotion As An Intervening Variable In The Office Of The Regent Of Langkat - Hairul Amin Ritonga; M. Chaerul Rizky (International Journal of Management, Economic and Accounting, 2025)
In recent decades, human resource management (HR) is the most important asset owned by a company. Human resource management is a very important and most responsible part of human resource management. In order for employee performance to be optimal, it is necessary to have a promotion as a company appreciation for the efforts that have been made by employees. The results of this study are that Competence has a positive and insignificant effect on Work Achievement with the original sample value of 0.251 and p values of 0.081. Competency had a positive and significant effect on Position Promotion with an original sample value of 0.567 and p values of 0.000. The training had a positive and insignificant effect on Work Achievement with the original sample value of 0.230 and p values of 0.060. Pelathan had a positive and significant effect on Position Promotion with the original sample value of 0.350 and p values of 0.013. Position promotion had a positive and significant effect on Work Performance with an original sample value of 0.478 and p values of 0.000. Competence has a positive and significant effect on Work Performance through Position Promotion with an original sample value of 0.271 and p values of 0.002. Training had a positive and significant effect on Job Achievement through Position Promotion with an original sample value of 0.167 and p values of 0.027.